(untitled) (Research, Society and Development, 2021)
Poultry is a well-developed and important activity for Brazil. However, it is an activity that generates waste, especially solid ones, such as bedding. As an alternative to reduce the environmental impact and production costs of the activity, many poultry farmers use the reuse of bedding for several consecutive batches. Knowing that the reuse of the bed takes place in a few batches only, it is necessary at some point to carry out the disposal of the bed. One of the possible ways for treatment (reduction of the risk of pollution) is the biodigestion process. Thus, the aim of this review was to approach biodigestion as an alternative for the sustainability of domestic poultry farming. The method used was a review in the bibliographic field of an exploratory nature on the waste generated in the activity, the biodigestion process, the use of inoculum and the predominant types of biodigesters. It is concluded that, through the biodigestion of chicken litter, the producer produces fuel for energy generation at a low cost, correctly manages the farm’s waste, in addition to contributing to the environment, reducing the possible environmental impacts produced in the poultry activity, making the activity a sustainable production model, without loss of meat production.